Correlation of the Imbalance in the Circulating Lymphocyte Subsets With C-Reactive Protein and Cardio-Metabolic Conditions in Patients With COVID-19 - Tyurin, Anton V.; Salimgareeva, Milyausha K.; Miniakhmetov, Ildar R.; Khusainova, Rita I.; Samorodov, Alexandr; Pavlov, Valentin N.; Kzhyshkowska, Julia (Frontiers in Immunology, 2022)
The immune system is severely compromised in patients with COVID-19. The representative group of 43 patients were selected from the cohort of 342 patients with COVID-19 and pneumonia. This group of 43 patients was examined for the levels of C-reactive protein, biomarker of systemic inflammation, and for the subsets of adaptive immune cells. The immunological parameters were correlated with the metabolic parameters and cardiovascular pathology history. We identified that a decrease in the absolute number of T-lymphocytes, T-cytotoxic, T-activated and B-lymphocytes correlated with the higher levels of CRP. The absolute number of T-helpers and the absolute number of double positive T-lymphocytes positively correlated with the levels of iron in serum (Z= 0,310 and Z=0,394). The absolute numbers of T-activated lymphocytes positively correlated with serum levels of LDH (Z = 0,422), ferritin (Z = 0,407) and iron (Z = 0,418). When studying subpopulations of lymphocytes, depending on the combined pathology, we found that the absolute numbers of B-lymphocytes and double positive T-lymphocytes in the peripheral blood were significantly reduced in patients with arterial hypertension (p=0,0074 and p=0,0227, correspondingly). The increased levels of NK cell were found in patients with a history of coronary heart disease (p=0,0108). In addition, we found that deficiencies in the adaptive immune system correlated with the deficiencies in iron metabolism. The cardiovascular pathology upsets the balance in the adaptive and innate immune system in the circulation of patient with severe COVID-19.